STRATEGI PENGEMBANGAN EKOWISATA YANG BERKELANJUTAN: (Studi Pada Kawasan Bromo dan Tengger) - Permana, Willy Deni (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Sustainable Ecotourism Development Strategy : Study in the Bromo and Tengger Areas. Bromo is one of the most popular tourist destinations in Indonesia. Ecotourism is one of the solutions in the tourism industry to empower people and protect the environment. However, in the development of the Bromo tourist area, there are still several obstacles in efforts to empower the community and the environment. Therefore, a sustainable ecotourism development strategy in the Bromo tourist area is very important. This study uses a qualitative descriptive method by analyzing SWOT (Strengths, Weaknesses, Opportunities, and Threats). Data was collected through observation, literature study, and interviews. The data was then analyzed using SWOT analysis. The results of this study indicate four strategies for developing sustainable ecotourism, namely: 1. Developing a Strategy by Increasing Strength-Opportunity Factors in Ecotourism Development, 2. Developing Strategies by Strengthening Weakness-Opportunity Factors in Ecotourism Development, 3. Developing Strategies by Utilizing Strengths-Threats Factors in Ecotourism Development and 4. Strategy Formulation with Participatory